Morphological features of metaplasia and dysplasia of epithelium in Barret’s esophagus. - Vitkovska, S. V. (Морфологія / Morphologia / Morfologìâ, 2012)
The article presents the morphological features of metaplasia and dysplasia of epithelium in Barret’s esophagus. The role of biopsy in the diagnostic of Barret’s esophagus and results of morphological research in the choice of follow-up and treatment of patients is shown.